(untitled) - K G Rajbanshi (Rome, 1995)
Nepal is a landlocked country of about 20 million people. Agriculture is the mainstay of economy of the country; an it provides employment for 90 percent of the population and produces 60 percent of the GDP. The contribution of the fisheries sub-sector to the GDP is very small and the per capita fish availability is less than 1 kg. Of the total fish production of about 17,000 mt, aquaculture contributes about 10,000 mt; and the rest comes from the capture fisheries in the rivers and lakes. With the increasing demand for fish for local consumption as well as for export to the lucrative markets in India. His Majesty's Government has given priority in the Eight Five Year Plan for the development of culture in ponds, lakes and paddy fields.
Keywords: fisheries